Peningkatan Sumber Daya Pemuda Melalui Pelatihan Kepemimpinan untuk Menciptakan Pemuda yang Berdayasaing di Desa Sanrobone, Kecamatan Sanrobone, Kabupaten Takalar - Tasrik; Amir (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Leader and leadership are two concepts that are interrelated and cannot be separated. In this context, leadership training is considered an important need for Mizanul Ulum Islamic Boarding School as a partner in the community service program, which provides support through facilities, infrastructure and human resources for the smooth running of the training. This leadership training activity is a form of collaboration between service lecturers from the Faculty of Economics and Business (FEB), Management Science Study Program at the Indonesian Muslim University, and Mizanul Ulum Islamic Boarding School, Takalar Regency. The training applies lecture methods, active participation and discussion. The training program is implemented through several stages, including observation, preparation, implementation and evaluation. The results realized by the participants show that this training has provided useful knowledge and prepared the participants, especially young Islamic students, to face the challenges of increasingly fierce competition in the future.